DAMPAK PSIKOLOGIS TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP PEREMPUAN - Dies Nurhayati (Perspektif, 2007)
In Indonesia, criminal acts are so various, especially which place women as the victims. One of the forms or frightening criminal acts through women is sexual violence. Sexual violence that undergoes women frequently is classified to the serious human rights colliding or extra ordinary crime which not only causes physical suffer but also causes educational and psychological looses through the victims. The victims (women) have suffered layered suffers due to sexual violence suffering. By sexual violence, women have been conducted as the subordination of the men biological capacity besides his threatening educational future.